ON THE PROBLEM OF MODAL STATUS OF THE VERB LASSEN - A. A. Balakina (Вестник Кемеровского государственного университета, 2014)
The research describes the modern functional-grammatical specificity of the verb lassen in German, the influence of pre-grammatical changes in the semantics of the verb lassen on its present function. The following analysis shows the modal status of lassen is ambiguous. The historical data specify a possible reason to include lassen in the group of modal verbs: a deep history of the verb (along with modal verbs), its high degree of grammaticalization and its use without particle zu. Modal meaning of the verb lassen ‘to permit’, ‘to order’ is associated with the semantic component of another person’s will. As a modal verb, lassen has the functional-grammatical monosemanticity (permissive function) due to stability of its lexical semantics since Teutonic period (before grammaticalization).